(untitled) (Research, Society and Development, 2021)
Objective: To discuss the experiences in the remote teaching and monitoring process, with a view to care, in times of pandemic. Method: An experience report type study with a qualitative, descriptive and exploratory approach, carried out based on the experiences and interactions promoted through virtual meetings between professor, student-monitor and students of the Nursing Course, in the discipline of Methodology of Scientific Work, with 30-hour workload, from the Department of Nursing in Collective Health at the Federal University of Paraíba (UFPB). Results: The activities were planned and organized in three main stages, reception, development of the programmed content and closure. They developed synchronously and asynchronously, using the following platforms and applications: Google (Meet, Forms, Docs and Agenda), Moodle Classes, e-mail and Whatsapp. Most of the (15) students were female, thirteen (13) were approved (87%). In all synchronous meetings, different cultural resources and strategies for the care and promotion of health (songs, poems, parables and ice breaking dynamics) were used to welcome, develop and close the activities. The monitoring was dynamic and creative using information and communication technologies. Conclusion: Teaching and monitoring with a view to care and health promotion, were a challenge in times of pandemic, a unique experience and an important component of contribution to the success of the academic education process in the format of remote teaching. A new look and way of doing was developed that allowed advancing and taking care of the teaching-learning process.